CHILDREN’S EDUCATION AS PERPETUAL CHARITY: A THEMATIC STUDY OF THE PROPHET’S HADITH - Nur Mawaddah Islamiyah; Romlah Abu Bakar Askar; Abdul Ghofur (PT. Jurnal Center Indonesia Publisher, 2025)
The hadith of Prophet Muhammad (peace be upon him) mentions three deeds that continue to benefit a person after death: ongoing charity (ṣadaqah jāriyah), beneficial knowledge, and a righteous child who prays for their parents. This hadith conveys a profound message about the importance of child education as a spiritual investment. This article aims to examine the urgency of children’s education from the perspective of this hadith by exploring the spiritual and social significance of having a righteous child as a continuous source of reward. This study employs a qualitative approach through library research, drawing on collections of hadith, classical Islamic literature (turas) such as the works of Imam al-Ghazali, Ibn Qayyim al-Jawziyyah, and Imam Nawawī, as well as contemporary references from nationally accredited journals. The findings indicate that educating children possesses a transcendental dimension, making it a form of ongoing charity for parents—especially when the child grows to be righteous and contributes positively to society. This research recommends that the concept of child education should not be viewed solely from a worldly perspective but should also be instilled as part of eschatological awareness within the Islamic education system.